PROBLEMATIKA EKSEKUSI PUTUSAN PENGADILAN TATA USAHA NEGARA - Rumadan, Ismail (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
The existence of the Administrative Court in the judicial system in Indonesia as a manifestation of the commitment of the state to provide legal protection of individual rights and the rights of the general public so as to achieve harmony, harmony, balance, and dynamic and harmonizing the relationship between citizens and the State. But the execution of the decision of the Administrative Court which have permanent legal force by the State Administration officials are not fully effective, although the mechanisms and the stages of execution has been carried out. Factors causing poor execution of the decision of the Administrative Court, among others; absence of rule of law that forced the officials to implement the State Administrative Court's decision: the commandment of the judge's decision that dare not include the forced payment of a sum of money when the state administration officials concerned did not implement the decision of the Court; factor and compliance officials in carrying out the State Administrative Court decision. Keywords: Execution, Judgment of the Court.